On the occurrence of the Bull Ray Pteromylaeus bovinus (Chondrichthyes: Myliobatidae) in the Amvrakikos Gulf, Greece - ZOGARIS, S.; DUSSLING, U. (Mediterranean Marine Science, 2010)
We document in this note the occurrence of the Bull Ray Pteromylaeus bovinus (Geoffroy St-Hilaire, 1817) (Chondrichthyes: Myliobatidae) in the Amvrakikos Gulf (eastern Ionian Sea), within a recently designated Wetlands National Park. Although distributional data for this species are scant, there is circumstantial evidence depicting the species as rare in Greece and the Mediterranean.